Pediatric pulmonary hemorrhage observed in non-vascular and vascular Ehlers–Danlos syndrome - Rong Yang; Haiming Yang; Chen Shen; Xingfeng Yao; Jinrong Liu; Huimin Li; Shunying Zhao (Orphanet Journal of Rare Diseases)
Abstract Background Ehlers–Danlos syndrome (EDS) is a heterogeneous group of heritable connective tissue disorders with varying features depending on the EDS subtype. EDS is associated with various respiratory manifestations. Pulmonary hemorrhage has been previously reported in vascular EDS (vEDS); however, this manifestation remains not particularly well-defined in other subtypes of EDS. This study extends the clinical understanding of EDS, particularly non-vascular EDS, and expands etiological spectrum of pulmonary hemorrhage in children. Methods We retrospectively analyzed the records of patients diagnosed with EDS between January 2020 and November 2024 at our institute. All clinical data was extracted from the electronic medical records, including clinical presentation, physical examination, family history, and chest computed tomography scans. EDS was confirmed based on clinical manifestations, pathological biopsies, immunohistochemistry, immunofluorescence staining, and genetic testing. Results Our study identified eight patients with EDS who presented with pulmonary hemorrhage. Among these eight patients, nine gene mutations were identified, including four in COL3A1, two in COL1A1, one in COL1A2, one in TNXB, and one in COL4A2. We identified the mutations: IVS44 + 1G→A and c.1550 C > T (p. Pro517Leu) of COL3A1 gene as two novel mutations associated with vEDS. And we added pathogenic evidences of the mutations c.1550 C > T (p. Pro517Leu) and c.3133G > A (p. Ala1045Thr) in COL3A1 gene. Conclusions Two novel and two pathogenic mutations in COL3A1 gene associated with vEDS, COL1A1, COL1A2, TNXB gene mutations of non-vascular types underlying EDS and COL4A2 gene associated with collagen synthesis were found in patients presenting with pulmonary hemorrhage. These findings would enhance clinical recognition of EDS and provide a sound basis to recommend that children with pulmonary hemorrhage be routinely examined for joint and skin hyperextension.